(untitled) (UNIZIK Journal of Marketing, 2026)
The paper studied the effect of market focus strategy on the sales performance of selected Small and Medium Scale Enterprises (SMEs) in Abia and Imo States, Nigeria. Market focus strategy of the study concentrated on geographical focus, product and service focus. And more importantly, how these segment strategies were used to achieve sales performance. Multi-stage probability sampling method was adopted for the study. The State was divided into three geo-political zones namely Abia North, Abia Central and Abia South. From each of these zones, 50 respondents were selected which gave us a sample size of 150. From here, 150 copies of copies of questionnaire were designed and distributed for collection of primary data for the study. Cronbach Alpha model was used to determine the reliability of the research instrument. And a result of 0.76 and 0.74 were adopted for test and re-test reliability of the instrument. The study revealed that market focus strategy has significant effect on the sales performance of the selected SMEs in Abia and Imo State. Specifically, geographical market focus strategy was significant than differentiation strategy on the sales performance of the selected SMEs. Further findings revealed that majority of the selected SMEs concentrated their limited resources to small customer group they can control. This led to increase in their sales volume over time. It was recommended that selected SMEs should adopt market focus strategy by focusing on specific group of customers in a particular market segment. Especially by those ones in table water who have little resources to compete with larger firms like Coca-Cola that and Pepsi that produce Eva Water and Aquafina respectively.